A Postcolonial Analysis of the One Plus-Africa Summits: A New Scramble for Africa? - Suleiman, Muhammad Reza; Omojuwa, Kayode (Institute of International Studies, 2025)
Since the colonial epoch, Africa has functioned as a crucible wherein global powers vie for influence and access to resources, imprinting enduring ramifications on the continent's international relations. Despite attaining political autonomy, Africa grapples with the persistent specters of neocolonialism and economic exploitation. The advent of Great Powers-Africa Summits marks a discernible juncture in global geopolitics, engendering discourse surrounding their underlying motivations and operational modalities. Critics caution that these summits risk perpetuating colonial vestiges, thereby potentially disenfranchising African agency while enabling continued exploitation. This study adopts a postcolonial analytical framework to comparatively scrutinize the Russia-Africa, China-Africa, and France-Africa summits, probing their historical antecedents, motivating factors, and resultant impacts. By advocating for more equitably configured paradigms of international engagement vis-à-vis Africa, this inquiry endeavors to foster the empowerment of African states, foregrounding imperatives of sovereignty, developmental progress, and dignified agency. By examining colonial legacies, divergent impetuses, consequential ramifications, and prospective models of collaborative engagement, this scholarly exposition furnishes nuanced insights into the negotiation of intricate postcolonial power dynamics and the advancement of African prerogatives within the global milieu.